Fatty Acids and an Ester from the Leaves of Millettia utilis Dunn - Ruksilp, Thanatip (Asian Health, Science and Technology Reports, 2020)
Two fatty acids, palmitic acid and oleic acid together with an ester, methyl oleate were isolated from dichloromethane crude extract from the leaves of Millettia utilis Dunn. The structures of all isolated compounds were elucidated by basic NMR spectroscopy and compared with previous literature. All compounds were tested for their antioxidant activities. Oleic acid revealed weak activity against ABTS assay with IC50 = 39.50 mg/mL.